Is Participation in Out-of-School Programs Linked to Students’ Health, Educational and Social Outcomes? - Enns, Jennifer; Brownell, Marni; Katz, Alan; Nickel, Nathan; Nie, Yao (International Journal of Population Data Science, 2018)
Introduction Out-of-school programs for grade K-12 students support healthy behaviours, boost academic achievement, and strengthen social networks. The Boys and Girls Clubs of Winnipeg (BGCW) have been active for 40+ years; however, little is known about how participating in their programs influences students’ short- and long-term health, educational and social outcomes. Objectives and Approach We are investigating the association between participation in BGCW out-of-school programs using the individual-level data held in the population-based Manitoba Population Research Data Repository at the Manitoba Centre for Health Policy (MCHP). Data on BGCW program participation for children born 1987-2010 was linked with administrative records from the healthcare system, education system, and social services. The comparison group of non-participants was matched on age, sex, 3-digit postal code and school division. Outcomes of interest include health services use, teen pregnancy, grade repetition, high school graduation, enrollment in post-secondary institutions, receipt of income assistance, and involvement with the justice system. Results We conducted analyses of children (K-8) attending the Community Schools Investigator (CSI) summer enrichment program, an academic and recreational program that aims to combat learning loss for children in low-income neighbourhoods. After one summer of CSI, participants (n=970) were significantly more likely to repeat a grade than the matched comparison group (n=783) (5.4% CSI students repeated a grade [95% CI 3.9, 6.8] vs 2.76% comparison students [95% CI 2.20, 3.32]). However, the likelihood of CSI students repeating a grade dropped to the level of the comparison group after two or more years of participation in CSI (2.91% CSI students repeated a grade [95% CI 1.26, 4.56]). Ongoing analyses are examining how participating in CSI and other BGCW programs is linked to health and social outcomes. Conclusion/Implications Our findings suggest that engagement in a BGCW out-of-school summer program contributes to better educational outcomes for low-income students. Using the information-rich Data Repository at MCHP, we can examine additional outcomes across multiple sectors to demonstrate how out-of-school programs help young people achieve their full developmental potential.